United Kingdom standards for non-invasive cardiac imaging: recommendations from the Imaging Council of the British Cardiovascular Society. Issue 21 (25th May 2022) - Treibel, Thomas A; Kelion, Andrew; Ingram, Thomas E; Archbold, R Andrew; Myerson, Saul G; Menezes, Leon J; Morgan-Hughes, Gareth J; Schofield, Rebecca; Keenan, Niall G; Clarke, Sarah C; Keys, Alan; Keogh, Bruce; et al.
Abstract : Heart and circulatory diseases affect more than seven million people in the UK. Non-invasive cardiac imaging is a critical element of contemporary cardiology practice. Progressive improvements in technology over the last 20 years have increased diagnostic accuracy in all modalities and led to the incorporation of non-invasive imaging into many standard cardiac clinical care pathways. Cardiac imaging tests are requested by a variety of healthcare practitioners and performed in a range of settings from the most advanced hospitals to local health centres. Imaging is used to detect the presence and consequences of cardiovascular disease, as well as to monitor the response to therapies. The previous UK national imaging strategy statement which brought together all of the non-invasive imaging modalities was published in 2010. The purpose of this document is to collate contemporary standards developed by the modality-specific professional organisations which make up the British Cardiovascular Society Imaging Council, bringing together common and essential recommendations. The development process has been inclusive and iterative. Imaging societies (representing both cardiology and radiology) reviewed and agreed on the initial structure. The final document therefore represents a position, which has been generated inclusively, presents rigorous standards, is applicable to clinical practice and deliverable. This document will be of value to a variety of healthcare professionals including imaging departments, the National Health Service or other organisations, regulatory bodies, commissioners and other purchasers of services, and service users, i.e., patients, and their relatives.